Characterization of purified cellulase from fermentation of sewage sludge - Mukhtaruddin, Muna Tasnim; Alam, Md. Zahangir; Hamzah, Mohd. Salleh (2011)
The increasing volume of sewage sludge as well as the municipal and agricultural waste produced and the total managing cost every year has been one of the major environmental issues in Malaysia. The production of cellulase from domestic sewage sludge could possibly bring an economic importance in certain industries as well as a key to solve the problem of environmental pollution and also in developing and utilizing renewable energy sources by applying the enzyme on the cellulosic materials. This study focuses on the characterization of cellulases produced from fermentation broth of sewage sludge. Using the cellulase enzyme with the activity of 45 U/ml, few tests have been carried out to characterize and checked the stability of the enzyme. The tests were pH stability, temperature stability as well as incubation time for the enzyme. Characterization of the enzyme was likely to help develop efficient application of the enzyme in industrial scale. 50oC was found to be the optimum temperature for the stability of the enzyme. Besides, pH 3 gave the highest enzyme activity and also 48 hours turn to be the optimum incubation time.